Digital video production: an invitation to creativity in Mathematics classes - Sílvia Mourão Meireles; Juliano Schimiguel (Educação Matemática Debate)
The promotion of creativity in Mathematics lessons fosters an environment conducive to the development of active participants in their knowledge construction process. The approach to mathematical content through video production offers significant potential for teaching and learning. The study, of a qualitative nature, sought to reflect on how video production can stimulate creativity in Mathematics classes. The investigation was conducted at a technical school in the city São Paulo with 29 students from the Integrated Technical High School program. The analysis reveals that the act of producing videos supported the construction of knowledge in Analytical Geometry and that this practice provides an opportunity for a creative approach to the communication of mathematical ideas.